Skrining Kesehatan Remaja Kolaborasi Institut Kesehatan Helvetia Medan dan Universiti Sultan Zainal Abidin Malaysia di SMP Amanah 1 Medan - Fitri Aidani Ulfa Harahap; Ekawaty Suryani Mastari (Yayasan Daarul Huda Kruengmane, 2025)
Adolescent health screening is an important strategy for the early detection of common health problems among school-aged students. This activity was conducted through an academic collaboration between the Institut Kesehatan Helvetia (IKH) Medan, Indonesia, and Universiti Sultan Zainal Abidin (UniSZA), Malaysia, as part of an international community engagement program. The health screening program implemented at SMP Amanah 1 included anthropometric measurements, blood pressure assessment, personal hygiene evaluation, nutritional status assessment, and identification of basic health complaints. The purpose of this activity was to obtain an overview of students’ health status while simultaneously increasing their awareness of the importance of healthy lifestyle behaviors. The program was carried out using a structured approach involving direct physical examinations, brief interviews, and health education sessions. The screening results indicated that a proportion of students were still at risk of nutritional problems and exhibited unhealthy lifestyle habits. International academic collaboration enhanced the quality of the screening process through the exchange of examination practices and educational approaches. This activity is expected to serve as a promotive–preventive model that can be implemented in other school settings. Overall, the screening program made a meaningful contribution to efforts to improve adolescent health, increased students’ understanding of the importance of regular health monitoring, and strengthened teachers’ capacity to support healthy habits at school. Furthermore, the screening findings may serve as a basis for developing more targeted follow-up health interventions. Thus, health screening based on international collaboration has significant potential to strengthen adolescent health in the long term.